Otomatisasi Pemberkasan Arsip Aktif Elektronik Pada Aplikasi Layanan Administrasi Mahasiswa - Fathurrohman, Fathurrohman (Khazanah: Jurnal Pengembangan Kearsipan, 2024)
Business information systems, namely electronic-based service applications usually don't automatically provide active archive filing features for electronic records generated from the business information system. Electronic Records are information contained in electronic files and media, which are created, received, or maintained by organizations or individuals and store them as evidence of activities. Like conventional records, electronic records that are created must be filed systematically and logically according to the context of their activities so that they become one file that has information relationships, similar types or similar problems. Student academic administration services at FMIPA IPB produce "born electronic" records. This study aims to design file automation on all electronic records created in the online academic administration service of FMIPA IPB students. The data collection method uses a literature study model, literature and interviews. The design technique of the electronic records filing system uses a waterfall model, while the system testing technique uses the black box technique. The results of the study produced an electronic records filing automation feature in the academic administration service FMIPA IPB so that it can assist organizations in filing electronic records in the academic section and automation of providing the list of active records.